Condensed Supramolecular Helices: The Twisted Sisters of DNA. (3rd December 2021) - Du, Guanqun; Belić, Domagoj; Del Giudice, Alessandra; Alfredsson, Viveka; Carnerup, Anna M.; Zhu, Kaizheng; Nyström, Bo; Wang, Yilin; Galantini, Luciano; Schillén, Karin
Abstract: Condensation of DNA helices into hexagonally packed bundles and toroids represents an intriguing example of functional organization of biological macromolecules at the nanoscale. The condensation models are based on the unique polyelectrolyte features of DNA, however here we could reproduce a DNA‐like condensation with supramolecular helices of small chiral molecules, thereby demonstrating that it is a more general phenomenon. We show that the bile salt sodium deoxycholate can form supramolecular helices upon interaction with oppositely charged polyelectrolytes of homopolymer or block copolymers. At higher order, a controlled hexagonal packing of the helices into DNA‐like bundles and toroids could be accomplished. The results disclose unknown similarities between covalent and supramolecular non‐covalent helical polyelectrolytes, which inspire visionary ideas of constructing supramolecular versions of biological macromolecules. As drug nanocarriers the polymer–bile salt superstructures would get advantage of a complex chirality at molecular and supramolecular levels, whose effect on the nanocarrier assisted drug efficiency is a still unexplored fascinating issue. Abstract : Chiral bile salt biosurfactant with low molecular weight can self‐assemble into supramolecular helices by interaction with oppositely charged polymers. A controlled condensation of the supramolecular helices into DNA‐like hexagonally packed bundles and toroids can be achieved when using block copolymers of opposite charge and increasing the bile salt content.